Numerical taxonomy (1973)
For some strange reason the attitudes of taxonomists and systematists towards the phrase "numerical taxonomy" fall into two extreme positions. On the one hand are those who think numerical taxonomy provides the only means of reaching objective conclusions, that any other approach to taxonomy is sterile, subjective, and really not quite scientific. At the other extreme are those taxonomists who think numerical taxonomy has no place in their science, that it is unclean or is likely to be the death of taxonomy.